Agenda Setting and Issue Definition at the Micro Level: Giving Climate Change a Voice in the Peruvian Congress. (17th October 2013) - Takahashi, Bruno; Meisner, Mark
<x xml:space="preserve">Abstract</x> Agenda‐setting and policy‐formulation processes, including those involved in global issues such as climate change, have been a focus of continuous research during recent years. Most studies have taken a broad, longitudinal perspective, with limited emphasis on the individual level decision making that can better explain the broader dynamics tested in the past. This study presents an analysis at the micro level that uncovers specific instances of individual decision making within an information‐processing framework. Additionally, little is known about how climate change is defined in developing nations that are highly vulnerable to its effects. This micro‐level analysis focuses on national legislators and advisers in the Peruvian Congress. The article presents a detailed narrative of the formulation process of several climate change bills and the development of a special committee on climate change and biodiversity in the 2006–2011 legislative period in the Peruvian Congress. The study discusses the role of policy entrepreneurs, the influence of limited or inaccurate information, and the competition with other policy issues through an analysis of in‐depth interviews with these legislative elites. The results show the significant influence of media reports and Internet use in a low‐information environment.